(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: In general entrepreneurship is the ability of the person covering his/her skill of employing innovation creation, imitation risk-bearing, leadership in the organized way. It provides opportunity to a person means of earning by giving self- employment and in providing employment to others. In the present scenario there is earnest need for attracting the educated youth towards in entering the of entrepreneurship instead of running behind the government jobs. In this reference the attitude towards entrepreneurship should be cared and studied empirically. Thinking on these lines in present investigation a comparison of male and female undergraduate students on their degree of attitude of towards entrepreneurship has been studied in relation to the level of academic –achievement on the sample of 1048 undergraduate students of Shri Rawatpura Sarkar University Raipur in the state of Chhatisgarh.The attitude of subject towards entrepreneurship was assisted was using self-developed tool. The studied that: Male high academic achiever for better than to those with low academic achiever. Whereas the finding are reversed in case female students. However the female students were found to have better attitude towards entrepreneurship to their male counter parts either high or low academic achievement.